Business Model Innovation Through MSME Sister Business - Alhidayatullah, Alhidayatullah; Amal, Muhammad Khairul; Kartini, Tina; Sudarma, Ade (International Journal of Law Policy and Governance, 2022)
This study aims to determine the effectiveness of the MSME sister business model related to production, marketing, and quality control. This MSME sister business model begins with conducting field observations first, to get Pioneer MSMEs and Assisted MSMEs. Business model innovation is a very important foundation for MSME players. This type of research is descriptive with a qualitative approach with interview methods and field observations of 4 Pioneer MSMEs and 50 Assisted MSMEs. From the results of field observation, 4 Pioneer MSMEs were obtained, namely food, mushroom cultivation, bamboo handcraft, wooden handcraft, and 50 Assisted MSMEs. After that, the equalization of perceptions regarding the MSME sister business model was carried out, training, workshops, and then business cooperation (matching business) was carried out. The contribution of this research is the resolution of the problems faced by MSMEs so far, especially the pros. The plan is to form Pioneer MSMEs and other Assisted MSMEs, to produce better economic growth in Sukabumi Regency in particular and Indonesia in general.